2018
DOI: 10.1007/s10928-018-9601-1
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of praziquantel pharmacokinetics to a pediatric population: a cautionary tale

Abstract: L-praziquantel (PZQ) pharmacokinetic data were analyzed from two relative bioavailability Phase 1 studies in adult, healthy subjects with two new oral dispersion tablet (ODT) formulations of L-PZQ administered under various combinations of co-administration with food, water, and/or crushing. Linear mixed effects models adequately characterized the noncompartmental estimates of the pharmacokinetic profiles in both studies. Dose, food, and formulation were found to significantly affect L-PZQ exposure in both stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Racemic praziquantel (PZQ) is the World Health Organisation (WHO)'s drug of choice to treat Schistosomiasis (WHO, 2009), a neglected tropical disease affecting 207 million people worldwide (WHO, 2018). Given the prevalence of this disease in young children (3 months to 6 years) (Stothard et al, 2011), the Pediatric Praziquantel Consortium (http://www.pediatricpraziquantelconsortium.org) aims to develop a pediatric formulation for this population (Bonate et al, 2018). Considering the recommendations from Research and Training in Tropical Diseases on switching to an enantiomerically pure formulation of the active form R-PZQ (WHO, 2007), one goal of the Pediatric Praziquantel Consortium was to clinically compare racemic (rac-PZQ) vs pure R-PZQ formulations (WHO, 2010), with the expectation that an enantiomeric pure formulation will result in a smaller orally disintegrating tablet (ODT) with less bitter taste, as inactive S-PZQ mainly contributes to unpleasant taste (Meyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Racemic praziquantel (PZQ) is the World Health Organisation (WHO)'s drug of choice to treat Schistosomiasis (WHO, 2009), a neglected tropical disease affecting 207 million people worldwide (WHO, 2018). Given the prevalence of this disease in young children (3 months to 6 years) (Stothard et al, 2011), the Pediatric Praziquantel Consortium (http://www.pediatricpraziquantelconsortium.org) aims to develop a pediatric formulation for this population (Bonate et al, 2018). Considering the recommendations from Research and Training in Tropical Diseases on switching to an enantiomerically pure formulation of the active form R-PZQ (WHO, 2007), one goal of the Pediatric Praziquantel Consortium was to clinically compare racemic (rac-PZQ) vs pure R-PZQ formulations (WHO, 2010), with the expectation that an enantiomeric pure formulation will result in a smaller orally disintegrating tablet (ODT) with less bitter taste, as inactive S-PZQ mainly contributes to unpleasant taste (Meyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of an empirical model based on statistical criteria may not lead to an accurate or acceptable model from a practical perspective. Cella et al [27], Santen et al [28], and Bonate et al [29] found that, despite statistical validation, a POPPK model may not predict PK parameters in a new population.…”
Section: Discussionmentioning
confidence: 99%
“…The shapes of the individual concentration/time profiles were highly variable with early and late C max , broad and sharp peaks, and multiple peaks. Overall between‐subject variability was very high, which hindered the construction of reliable population PK models that would permit extrapolation of adult PK data to children . The lower bioavailability of L‐PZQ ODT, the high variability and the nondose linearity of the PK parameters indicated the need for a proper pediatric dose‐finding study.…”
Section: Discussionmentioning
confidence: 99%